Diagnosing multiple system atrophy: current clinical guidance and emerging molecular biomarkers - Goolla, Meghana; Cheshire, William P.; Ross, Owen A.; Kondru, Naveen (Frontiers in Neurology, 2023)
Multiple system atrophy (MSA) is a rare and progressive neurodegenerative disorder characterized by motor and autonomic dysfunction. Accurate and early diagnosis of MSA is challenging due to its clinical similarity with other neurodegenerative disorders, such as Parkinson’s disease and atypical parkinsonian disorders. Currently, MSA diagnosis is based on clinical criteria drawing from the patient’s symptoms, lack of response to levodopa therapy, neuroimaging studies, and exclusion of other diseases. However, these methods have limitations in sensitivity and specificity. Recent advances in molecular biomarker research, such as α-synuclein protein amplification assays (RT-QuIC) and other biomarkers in cerebrospinal fluid and blood, have shown promise in improving the diagnosis of MSA. Additionally, these biomarkers could also serve as targets for developing disease-modifying therapies and monitoring treatment response. In this review, we provide an overview of the clinical syndrome of MSA and discuss the current diagnostic criteria, limitations of current diagnostic methods, and emerging molecular biomarkers that offer hope for improving the accuracy and early detection of MSA.